Caregivers’ Perceptions of a Youth-led Sexual Violence Prevention Initiative: A Brief Report - Edwards, Katie M. (Journal of interpersonal violence, 2022)
Sexual and related forms of violence among middle and high school students are pervasive public health issues, and thus, there is a growing emphasis on the development and evaluation of sexual violence prevention efforts for youth. Caregivers such as parents are important partners in this work as they can facilitate youths? involvement (e.g., give them permission to participate, provide instrumental support such as rides), but their perception of their youth?s involvement in sexual violence prevention efforts is largely unexplored. The current paper examined caregivers? perceptions of their teens? participation in a community-wide, out-of-school, youth-led sexual violence prevention initiative. Some caregivers of youth who were involved in the initiative (N = 19; 79.9% White; 21.1% Native American) responded to closed- and open-ended questions about what their teen had talked to them about in relation to the initiative, why their teen participated in the initiative, and how involvement impacted their teen. Furthermore, caregivers who attended events themselves responded to questions about what they learned, what they liked best, and what they liked least. Over half of caregivers said that their teens talked to them about bystander intervention, social emotional skills, and what constitutes sexual violence. Perceptions of the initiative were largely positive both in terms of what the teen learned at part of the programming and in caregivers? own experience participating. These results are promising for the role of caregivers in partners in prevention.